De profundis: A theological-aesthetic reading of the poem «Los heraldos negros» («The Black Heralds») - Báez Rivera, Emilio Ricardo (2022)
César Vallejo gives to the poem «Los heraldos negros» the weight of an epigraph to the book bearing the same title with the purpose of encapsulating the dominant tone of a lyrical voice subdued, mainly, by the insufficient of language in that initiatory and opening poem. The lyrical self leads from simple literary tools, such as simile, to more complex ones, such as metaphor. Vallejo’s lyrical voice is presented as an equalizing force that does not pretend to exempt itself, according to Christian theology, from the suffering that is guaranteed by the natural order.